Relationship between motivation, learning habit and overall results of polytechnic mechanical engineering student - Akasyah Mohd Khathri; Che Haspu Robiah Daud (Journal of Counseling and Educational Technology, 2018)
Motivation and learning habit generally play an important role in influential the results of a student's exam. This study aims to determine the relationship between motivations, learning habit and overall achievement in the second semester of Mechanical Engineering students at Terengganu Polytechnic. The study also aims to identify the differences in learning by gender at early achievement in the previous semester. To achieve this goal, the method of survey is conducted. Samples consisted of 196 students in second semester out of four programs in Mechanical Engineering Department. The study instrument used was Selmes Learning Inventory which presented four learning styles, namely deep-style, surface-style, well-organized style and diligent. The fifth style of learning, motivational style has been modified to measure the internal and external motivation. Data collected were analyzed descriptively and inferred using SPSS software. The results of the descriptive analysis found that students had high internal motivation as compared to external motivation as well as practicing surface style and deeper style than planned and diligent style. Inferential analysis results found that the overall achievement of the second semesters had a relationship with the in-depth learning style, effort and planning. There is a significant relationship between deep learning style and internal motivation. There was no significant difference in learning habit by gender and early achievement. The implication of this study is that motivation plays an important role in determining the choice of learning methods practiced by the students.